MOSIS: a moisture sensor structure and interfacing system for the on-line measuring of the moisture content of plaster cardboard plates - Geeraerts, B.; Sansen, W. (1996 IEEE Instrumentation and Measurement Technology Conference Proceedings, 1996)
A new measurement technique and system was developed to remotely sense the moisture content of plaster cardboard plates during fabrication. The measurement system, which was called MOSIS, consists of custom built parts. Dedicated sensor structures capable of sensing very small variations in moisture content (smaller than 0.5%) were developed. Furthermore, a modular electronic signal conditioning and processing system was designed and assembled. An ordinary personal computer with a dedicated graphical user interface controls the MOSIS system and displays on-line the recorded multi-channel moisture content variations. Several measurements were carried out at a commercial plaster cardboard plate production plant and are still continuing.